PENGARUH LIVE STREAMING DAN FLASH SALE TERHADAP PERILAKU IMPULSE BUYING - Jerry Sastiawan Perdana; Meiffa Herfianti (UM. Bengkulu, 2026)
The development of digital technology and social media has led to significant changes in consumer behavior, particularly among Generation Z. TikTok Shop, as a social commerce platform, utilizes live streaming and flash sale features as major marketing strategies to attract consumers’ attention. These features are considered capable of creating emotional stimulation and a sense of urgency that can trigger impulse buying behavior. This study aims to analyze the effect of live streaming and flash sale on impulse buying behavior on TikTok Shop (A Study on Generation Z at Universitas Muhammadiyah Bengkulu). This study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to Generation Z students at Universitas Muhammadiyah Bengkulu and analyzed using statistical tests, including t-tests and F-tests, to determine the partial and simultaneous effects among variables. The method used was proven to be effective in measuring the relationship between live streaming, flash sale, and impulse buying behavior. The results show that the live streaming variable (X1) has a positive and significant effect on impulse buying behavior with a significance value of 0.002 < 0.05, indicating that Ha is accepted and Ho is rejected. The flash sale variable (X2) also has a positive and significant effect on impulse buying behavior with a significance value of 0.000 < 0.05, indicating that Ha is accepted and Ho is rejected. Simultaneously, live streaming and flash sale have a significant combined effect on impulse buying behavior on TikTok Shop. This indicates that the combination of real-time interaction, attractive product visualization, limited- time promotions, and exclusive offers encourages consumers to make spontaneous purchases without prior planning. The conclusion of this study confirms that marketing strategies through live streaming and flash sale are proven to be successful, effective, and play an important role in increasing impulse buying behavior among Generation Z at Universitas Muhammadiyah Bengkulu. Therefore, this study provides empirical evidence that the integration of live streaming and flash sale is a key factor in shaping impulsive buying behavior in the digital era. Keywords: live streaming, flash sale, impulse buying, TikTok Shop, Generation Z